Stratigraphy Of The High Juran Carbonate Formation With Oil And Gas In The Bukhara-Khiva Region - Rabbimov Jakhongir Shodmonkulovich; Temirov Toxir Turgun ugli (Stanford Database Library of American Journal of Applied Science and Technology, 2026)
Paleontological and stratigraphic studies play an important role in increasing the efficiency of oil and gas exploration. While these studies help determine the boundaries of the exploration area, they also ensure the determination of the location of trap areas and sections belonging to the non-anticlinal group and the identification of reefs in the bodies of fossil carbonate strata.